The Contribution of Risk Management to Profit and Cost Efficiency in Rural Shariah Banks (BPRS) - Anggraeni Anggraeni (Proceedings of AICS - Social Sciences, 2016)
The development of Shariah baking in Indonesia has been so tremendous that the banks should try their efforts to improve their operation. Risk management is vital to be implemented in order that the operation can minimize any risk. This study examines the impact of risk management practice on the profit and cost efficiency in the rural Islamic banks. The data were collected from 33 BPRS but only 29 could be analyzed using the current software. This study also tried to implement better software for financial report. Initially, the initial report shows that, on average, the efficiency is 64% in which the minimum is 30% and maximum is 100%. In fact, only five banks could achieve the efficiency that is from 29 banks during the investigation. From city of origin, it was found that the banks in Pasuruan and those which are in Probolinggo are the most efficient.